2019
DOI: 10.1103/physrevd.100.076019
|View full text |Cite
|
Sign up to set email alerts
|

Heavy quarkonium suppression beyond the adiabatic limit

Abstract: Many prior studies of in-medium quarkonium suppression have implicitly made use of an adiabatic approximation in which it was assumed that the heavy quark potential is a slowly varying function of time. In the adiabatic limit, one can separately determine the in-medium breakup rate and the medium time evolution, folding these together only at the end of the calculation. In this paper, we relax this assumption by solving the 3d Schrödinger equation in real-time in order to compute quarkonium suppression dynamic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 49 publications
0
36
0
Order By: Relevance
“…1 This approximation allows us to straightforwardly go beyond previous phenomenological works which made use of the adiabatic approximation instead of real-time solutions [20,[45][46][47][48][49][50][51][52][53]. In a previous paper [54], we made a preliminary investigation of the effects of relaxing the adiabatic approximation, finding that there were potentially important effects on the survival probability of the states.…”
Section: Introductionmentioning
confidence: 99%
“…1 This approximation allows us to straightforwardly go beyond previous phenomenological works which made use of the adiabatic approximation instead of real-time solutions [20,[45][46][47][48][49][50][51][52][53]. In a previous paper [54], we made a preliminary investigation of the effects of relaxing the adiabatic approximation, finding that there were potentially important effects on the survival probability of the states.…”
Section: Introductionmentioning
confidence: 99%
“…For the background, Ref. [60] considered a transversally homogeneous and boost-invariant ideal fluid with a temperature which decreases as T (τ) = T 0 (τ 0 /τ) 1/3 . In Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In order to go beyond the adiabatic approximation one can instead solve the time-dependent Schrödinger equation with a time-dependent complex in-medium heavy quarkonium potential. In a recent paper [60], it was demonstrated that one can numerically solve the Schrödinger equation in real-time using an efficient split-operator method and extract the survival probability directly from the final quantum wave function. In this case, one uses time-dependent eigenstates and computes the overlap of these with the time-evolved wave function.…”
Section: First Steps Beyond the Adiabatic Approximationmentioning
confidence: 99%
See 2 more Smart Citations